EXPLORATION OF CHALLENGES ENCOUNTERED IN DIGITAL RECRUITMENT (CAHIERS MAGELLANES-NS, 2024)
The advent of e-recruitment has revolutionized the hiring process, offering convenience, efficiency, and access to a broader pool of candidates. However, this transition has brought about a unique set of challenges for organizations seeking to leverage digital platforms for talent acquisition. This study delves into the multifaceted challenges encountered in e-recruitment practices, aiming to provide a comprehensive understanding of their impact on organizational recruitment strategies. Through a synthesis of existing literature and empirical analysis, the research explores issues such as attracting high-quality candidates amidst fierce online competition, effectively managing the influx of applications, safeguarding data security and privacy, addressing biases inherent in algorithmic selection processes, and nurturing a positive candidate experience in a digital environment. By examining these challenges in depth, this study seeks to offer valuable insights into the complexities of e-recruitment and provide recommendations for organizations to navigate these obstacles effectively, thereby optimizing their recruitment processes and enhancing overall organizational performance.